An evaluation of interpretive media at the Dillon Nature Center - Mullins, Christopher (Kansas State University, 2016)
Dillon Nature Center has a wide variety of exhibits that teach the public about the natural resources of Kansas. The purpose of my study was to conduct an exploratory study about the effectiveness of two key exhibits in the nature center (Underground Theater and Tornado), as well as evaluate the use of Quick Response Code or QR codes along one of the trails. A visitor survey was used to collect these data over 30 3- hour sampling periods. One hundred and ninety-five visitors were surveyed during the extent of my study. Fifty-four of those who were surveyed went into the Underground Theater exhibit and 47 went into the Tornado exhibit. I concluded that the Underground Theater exhibit was successful in providing useful information to the visitor, whereas the Tornado exhibit provided little useful information to the visitor. Visitors slightly preferred the use of QR codes along the trail even though the actual use was low. This study indicated that the type of exhibit greatly impacts what the visitor takes away from the exhibit. I also showed that it is likely people prefer newer technology to be available at the nature center. These findings provided the management and staff of Dillon Nature Center with information to guide their interpretive-planning efforts.
Keywords: Interpretive media; Dillon Nature Center; Zones of Tolerance; QR codes; Kansas; Parks and Recreation